Immigration and work - Agius Vallejo, Jody. (Bingley, U.K. : Emerald, 2015)
Immigrants and their descendants are growing populations that are rapidly changing the racial/ethnic diversity of the United States and many societies across the globe. People migrate for a multitude of reasons but work - whether in the high-skilled, low-wage, or informal sectors of the economy--or the drive to establish a business, is the primary impetus. The goal of this volume is to bring together new empirical research and theoretical innovations from cutting-edge scholarship concentrating on the intersection of immigration and work. Research in this volume investigates how larger structural inequalities in sending and receiving nations, immigrant entry policies, group characteristics, and micro level processes, such as discrimination and access to ethnic networks, shape labor market outcomes, workplace experiences, and patterns of integration among immigrants and their descendants.
Central American immigrant workers : how legal status shapes the labor market experience / Cecilia Menjívar -- Between support and shame : the impacts of workplace violations for immigrant families / Shannon Gleeson -- Intersectional differences in segmented assimilation : skill and gender in the context of reception / Zulema Valdez -- Economic progress, stagnation or decline? : occupational mobility of non-EU immigrants in Europe / Sonia Pereira, Erik Snel, Margrietha 't Hart -- Labor union activity and the civic participation of latino immigrant workers / Veronica Terriquez -- Embedded solidarity : International migrant labor advocacy in South Korea / Joon Kim -- Transnational entrepreneurship and immigrant integration : new Chinese immigrants in Singapore and the United States / Min Zhou, Hong Liu -- Adaptation and return among Israeli enclave and infotech entrepreneurs / Steven Gold -- Franchising ethnic entrepreneurship : immigrant business owners and an alternative economic model / Pawan Dhingra, Jennifer Parker -- A new gendered occupational niche: latina pathways into the teaching profession / glenda flores,pierrette hondagnue-sotelo -- Bridging boundaries of difference : intergroup contact between immigrants and natives in the context of work / Elizabeth Miller.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Emigration & Immigration; Social Science -- Sociology -- General; Sociology: work & labour; "Migration, immigration & emigration".; Emigration and immigration